Lunchtime rules - Steggall, Vicki; Illustrated by Oswald, Ash (Australia Prahan, 2005)
Ant (short for Samantha) loves playing footy with her friends at lunchtime. But when one of the boys decides she is too slow to play, it looks like everything is going to change. Can Ant's plan make lunchtimes fun again? Suggested level: primary.
Include Illustrations
Keywords: Girls -- Football stories -- Soccer stories